The Effectiveness of Scientific Argumentation Strategy towards the Various Learning Outcomes and Educational Levels Five Over the Years in Science Education - Indah Juwita Sari; R. Ahmad Zaky El Islami (Yayasan Keluarga Guru Mandiri, 2020)
This study aimed to investigate the effectiveness of scientific argumentation strategy towards various learning outcomes and educational levels five over the years in science education. This study was used systematic review and meta-analysis using R application. Selected ten articles from the Web of Science database during 2016-2020 were used in this study. The results showed that scientific reasoning is more effective for improving through scientific argumentation in the higher education level than other learning outcomes and other educational levels with an effect size 1.39 and standard error 0.2478. So, we can conclude that there is evidence to suggest using a scientific argumentation strategy in improving scientific reasoning in higher education levels both in the teaching process and the research.